2011
DOI: 10.1001/archinternmed.2011.283
|View full text |Cite
|
Sign up to set email alerts
|

Fast Food Restaurants and Food Stores

Abstract: Background A growing body of cross-sectional, small-sample research has led to policy strategies to reduce food deserts – neighborhoods with little or no access to healthy foods – by limiting fast food restaurants and small food stores and increasing access to supermarkets in low-income neighborhoods. Methods We used 15 years of longitudinal data from the Coronary Artery Risk Development in Young Adults (CARDIA) study, a cohort of U.S. young adults (n=5,115, 18–30 years at baseline), with linked time-varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
180
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(201 citation statements)
references
References 39 publications
14
180
6
1
Order By: Relevance
“…Fast food restaurants, non-fast food restaurants, supermarket, and convenience stores were aggregated as counts within 3 kilometers (km) of each respondent’s residential location (Euclidean buffer). The 3 km buffer was chosen to capture distances readily accessible by walking and driving to neighborhood diet-related resources as supported by several studies (Boone-Heinonen, Gordon-Larsen et al 2011; Hillier, Cannuscio et al 2011; Author et al 2011). Food resource densities were derived as counts per 10 km secondary roadway (roads used to connect smaller towns, subdivisions, and neighborhoods) and local roadway (roads used for local traffic, usually with a single lane of traffic in each direction), resulting in a measure of concentration of food resources along streets representing overall commercial activity(Romley, Cohen et al 2007; Richardson, Boone-Heinonen et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Fast food restaurants, non-fast food restaurants, supermarket, and convenience stores were aggregated as counts within 3 kilometers (km) of each respondent’s residential location (Euclidean buffer). The 3 km buffer was chosen to capture distances readily accessible by walking and driving to neighborhood diet-related resources as supported by several studies (Boone-Heinonen, Gordon-Larsen et al 2011; Hillier, Cannuscio et al 2011; Author et al 2011). Food resource densities were derived as counts per 10 km secondary roadway (roads used to connect smaller towns, subdivisions, and neighborhoods) and local roadway (roads used for local traffic, usually with a single lane of traffic in each direction), resulting in a measure of concentration of food resources along streets representing overall commercial activity(Romley, Cohen et al 2007; Richardson, Boone-Heinonen et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…An and Sturm 231 used data on children and adolescents from California and found no relationship between consuming a healthy diet and the food environment as measured by type of food outlets within 1.5 miles of the respondent's home or school. Using 15 years of longitudinal data from CARDIA Boone-Heinonen et al found that supermarket availability near the home is unrelated to diet quality or produce intake 232 .…”
Section: Introductionmentioning
confidence: 99%
“…Frequent fast-food consumption has been related to higher fat intake (12,1820) and poor health (2124) . Availability of FFR in one’s residential neighbourhood increases the likelihood of consuming fast foods (23,25,26) , having poor diet quality (12,27) and being obese (23,24,2830) . However, not all individuals within a given environment will have a poor diet or become obese; some studies did not find an association between residential neighbourhood availability of FFR and diet (3133) or obesity (32) , while some found the inverse to be true (greater neighbourhood FFR availability associated with lower BMI) (34) .…”
mentioning
confidence: 99%